Comment on Using Criminal Punishment to Serve Both Victim and Social Needs - Haley, John O. (2009)
Haley comments on the argument underlying the article by Erin Ann O'Hara and Maria Mayo Robbins, which emphasizes on victim-offender mediation (VOM). By expanding the frame of reference, restorative justice can be defined as a paradigm whose scope encompasses more than VOM and whose emphasis includes the needs of society and offenders as well as victims. Restorative justice involves a wide variety of processes and programs that are more apt to restore both those who commit and those who suffer wrongs. It includes children at risk programs, drug courts, violence-treatment programs, as well as VOM programs. It also includes efforts to assist former convicts returning to the community to engage in constructive lifestyles and sustainable roles in families, workplaces, and neighborhoods